Инновации в русскоязычном публичном дискурсе (на материале обсуждения важнейших событий 2020–2021 гг. в электронных СМИ) - Kapela, Ewa (Studia Rossica Posnaniensia, 2022)
The article describes the new words that appeared in the Russian language public discourse. They are connected with three political events that caused a wide public outcry: the All-Russian vote on the approval of amendments to the Constitution of the Russian Federation, protests in support of Sergei Furgal, the detained governor of the Khabarovsk Krai, and the poisoning of opposition leader Alexei Navalny. The research material was collected from online media from January 2020 to September 2021. It includes neologisms, neosemantisms, and new phrases, many of which are occasional. In the collected material there are innovations formed according to standard derivational models and words and phrases representing the product of wordplay, including lexical blends. The considered innovations, being a manifestation of democratization and carnivalization of public communication, perform not only a nominative function. Due to their novelty, unusualness, and expressiveness, they have an evaluative potential. These innovations often become a linguistic means of speech aggression. In addition, they reflect the current social and political events of concern to the society and the attitude of the linguistic community to what is happening.